A Foundation for Embedded Languages - Rhiger, Morten (BRICS Report Series, 2002)
Recent work on embedding object languages into Haskell use ``phantom types’’ (i.e., parameterized types whose parameter does not occur on the right-hand side of the type definition) to ensure that the embedded object-language terms are simply typed. But is it a safe assumption that only simply-typed terms can be represented in Haskell using phantom types? And conversely, can all simply-typed terms be represented in Haskell under the restrictions imposed by phantom types? In this article we investigate the conditions under which these assumptions are true: We show that these questions can be answered affirmatively for an idealized Haskell-like language and discuss to which extent Haskell can be used as a meta-language.